Smart cities: Understanding policies, standards, applications and case studies - Surender Reddy Salkuti (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper presents the integration of required basic facilities of living such as healthcare, education, and infrastructure for building the smart cities. The administrations of smart cities should have the smart governance, safety measures with cultural and social stimulus. Four building blocks of smart cities, i.e., people and environment, smart utilities, smart technology and smart administration are described in the present paper. The aim of this paper is to give a clearer perspective of the key decisions with spatial reference that may assume a key part in the plan of a smart city technique. Application of various technologies, for examples big data, artificial intelligence, machine learning, internet of things (IoT), cloud computing, block chain technology to the smart cities are discussed in this paper. Various challenges of smart cities such as information technology (IT) infrastructure, cost, privacy, security, efficiency, fossil fuel dependency and congested commutes with proposed solutions are also presented in this paper.